Translanguaging pedagogy model for multilingual EFL teacher development: Toward a sustainable approach from Northern Thailand - Santhi, Natthaphon; Dawilai, Sirikanya; Siririth, Weeraphan (Edelweiss Applied Science and Technology, 2026)
This study presents a translanguaging-based teacher development model designed to support English as a Foreign Language (EFL) teachers working in multilingual contexts in Northern Thailand. Based on a translanguaging pedagogical model, a 30-hour professional development program was implemented to promote classroom language use strategies, reflective practice, and professional empowerment among 120 primary and lower-secondary teachers across Chiang Rai, Chiang Mai, Phayao, and Nan provinces. Data were collected using a mixed-method design comprising: (1) a needs analysis questionnaire; (2) pre- and post-tests evaluating teachers’ language proficiency and pedagogical understanding; and (3) a satisfaction questionnaire, complemented by open-ended qualitative responses. The quantitative analysis showed strong teacher needs across the three areas of translanguaging practice: stance, design, and shifts. The overall mean of 4.19 indicated teachers’ readiness to apply translanguaging in classrooms. The teachers’ post-test mean increased from 40.16 to 51.21, indicating progress of 11.05. Teachers also rated their high satisfaction level with the model (overall mean = 4.43). The qualitative results highlighted teachers’ appreciation of Thai and local languages for emotional and pedagogical support. Many felt more confident using familiar languages to promote learning. Overall, the training appeared to strengthen confidence, foster flexible teaching, and encourage sustainable multilingual practices in EFL classes.